Adventure time. 2, Pixel princesses - Corsetto, Danielle (KaBOOM!, a division of Boom Entertainment, Inc., 2013)
"All LSP wants is a night to hang with her friends. But when things don't go as planned she finds herself questioning what it really means to be a princess. With a misplaced wish and a lot of battle training, LSP Embryo Princess, Breakfast Princess, Muscle Princess, and Turtle Princess find themselves on an adventure that none of them signed up for"--Page [4] of cover.